Pengaruh Komposisi Media Dasar dan Jenis Eksplan terhadap Pembentukan Embrio Somatik Kakao - Ajijah, Nur (Jurnal Tanaman Industri dan Penyegar, 2016)
The composition of basal medium determines the regeneration success of in vitro culture. The study aimed to evaluate the effect of basal medium in the primary callus induction medium and explant type on the formation of cacao somatic embryo. The research was conducted at the Tissue Culture Laboratory of IAARD, Bogor, from June 2014 to December 2015. Primary callus induction derived from staminoid and petal explants of ICCRI 4 clone used two types of basal medium, i.e. DKW+ 9 µM 2.4-D + 1.16 µM kinetin or WPM + 9 µM 2.4-D + 1.16 µM kinetin. After 14 days, callus was subcultured onto secondary callus induction medium (WPM + 2.4-D 9 μM + kinetin 0.58 μM), and then onto DKW medium without growth regulators to induce the formation of somatic embryo. The research was designed in two-factor factorial design with five replications. The first factor was the type of basal medium on the primary callus induction medium (DKW and WPM) and the second factor was the type of explants (petal and staminoid). The results showed significant interaction effect between basal medium type and explant type on the formation of callus and somatic embryo of cacao. The highest percentage of callus formation was derived from staminoid explants on the DKW basal salt medium (92.5%). However, the highest percentage of somatic embryo formation and the number of somatic embryo per explant were obtained from DKW basal salt medium with petal explants (36.5% and 2.3). Therefore, the use of DKW basal salt medium and petal explant were recommended for the induction of somatic embryo of the ICCRI 4 clone.